2018
DOI: 10.21037/jtd.2018.08.60
|View full text |Cite
|
Sign up to set email alerts
|

Serum decorin is a potential prognostic biomarker in patients with acute exacerbation of idiopathic pulmonary fibrosis

Abstract: Background: Decorin is a small leucine-rich repeat proteoglycan that plays a critical role in collagen fibrillogenesis, and regulates inflammation, wound healing and angiogenesis. In idiopathic pulmonary fibrosis (IPF), decorin is expressed in fibrotic lesions; furthermore, intratracheal gene transfer of decorin has been demonstrated to inhibit bleomycin-induced pulmonary fibrosis. Although these results suggest the critical role of decorin in pulmonary fibrosis, the role of decorin in the acute exacerbation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…IPF is strongly associated with gastroesophageal reflux disease [137], a condition where acid flow could modulate lung pH and potentially enhance cathepsin activity. CTSS-degraded decorin is also being investigated as a potential biomarker for fibrotic lung disorders including IPF [81] in addition to lung cancer [74]. Interestingly, the endogenous cathepsin inhibitor, cystatin C, is a possible biomarker for IPF [138].…”
Section: Lung Cancermentioning
confidence: 99%
“…IPF is strongly associated with gastroesophageal reflux disease [137], a condition where acid flow could modulate lung pH and potentially enhance cathepsin activity. CTSS-degraded decorin is also being investigated as a potential biomarker for fibrotic lung disorders including IPF [81] in addition to lung cancer [74]. Interestingly, the endogenous cathepsin inhibitor, cystatin C, is a possible biomarker for IPF [138].…”
Section: Lung Cancermentioning
confidence: 99%
“…The measure of hQOL was also described in one study. A total of eight research groups conducted multiple studies using the same cohort and published reports (Collard et al, 40 Kim et al, 50 Lee et al, 54 and Song et al 62 ; Kishaba et al 51 52 ; Enomoto et al [41][42][43] ; Furuya et al, 45 Isshiki et al, 46 Koyama et al, 53 and Sakamoto et al 59 ; Nikaido et al 55 and Sand et al 60 ; Kataoka et al, 48 Suzuki et al 64 and Yokoyama et al 71 ; Abe et al 35 and Atsumi et al 38 ; Tomioka et al 66 and Yamazoe et al 70 ; online supplementary e-table 1). Among these multiple research conducted by the same groups, the study with the largest sample size was prioritised and a total of 31 potential prognostic factors, which were investigated for their association with all-cause mortality, were identified and followed by further analysis (online supplementary e-table 2).…”
Section: Confidence In Cumulative Evidencementioning
confidence: 99%
“…Based on the combined result, APACHE II score was significantly associated with all-cause mortality of AE of IPF with an HR of 1.09 (95% CI 1.04 to 1.15;figure 1). The remaining one study excluded from metaanalysis demonstrated a higher APACHE II score for non-survivors although it was not statistically significant (MD 2.80 (95% CI −1.19 to 6.79)55 ; online supplementary e-table 4). A multivariate analysis reported by one study demonstrated a significant result with an HR of 1.10 (95% CI 1.01 to 1.19),49 which was consistent with…”
mentioning
confidence: 93%
“…Furthermore, serum decorin is a small, leucine-rich proteoglycan that has been introduced as a novel marker for AE of IPF. Nikaido et al [23] reported that serum decorin had a significant association with oxygenation. Further multicenter studies will be required for further validation.…”
Section: Biomarkersmentioning
confidence: 99%